Analysis Of The Physical Quality Of Odot Grass Silage With The Addition Of Sago And Tapioca Flour Additives As Goat Animal Feed In Werwawan Hamlet, Lakor Subdistrict, Southwest Maluku Regency - Sairudy, Albertus; Gairtua, Barnabas; Welerubun, Inggrid; Jesayas, Heryanus (Program Studi Di Luar Kampus Utama Universitas Pattimura, 2022)
The success of the livestock business is supported by several factors, one of which is feed. Feed is everything that can be eaten, digested both in part and in whole without disturbing the health of the livestock that consume it. Feed is needed by livestock to meet the living needs of both production, and reproduction. Indonesia has a tropical climate that has two seasons, namely the rainy season and the dry season. Forage feed production fluctuates following the season, in the rainy season the availability of forage of abundant feed, in the dry season forage is very minimal. To overcome the constraints of lack of forage availability of feed there needs to be an alternative/policy with rational considerations and young and cheap obtained. One alternative is utilizing the advantages of greenery available during the rainy season to be utilized during the shortage of forage, namely by means / methods of making silage. In the manufacture of silage, if the basic material is not considered good / low quality then, it is necessary to add additional feed (silage additives). In addition, the addition of silage additives that function silage additives is to act as a fermentation stimulant, as a fermentation inhibitor, and also act as a substract. The basic ingredients in the study are odot grass and additional feed (silage additives (sago flour and tapioca). The topic of this study is the Analysis of Physical Quality of Silase Grass Odot With the Addition of Sago And Tapioca Flour Additives as Goat Animal Feed in Werwawan Hamlet, Lakor Subdistrict, Southwest Maluku Regency.